Bioequivalence evaluation of epinephrine autoinjectors with attention to rapid delivery - Sclar DA (Dove Medical Press, 2013)
David Alexander Sclar Department of Pharmacy Practice, College of Pharmacy, Midwestern University, Glendale, AZ, USA Abstract: Timely and proper injection of epinephrine is critical to prevent serious consequences relating to anaphylaxis. In a recent bioavailability study comparing epinephrine delivery from the Auvi-Q™ and EpiPen® epinephrine autoinjectors, the Auvi-Q failed to meet the bioequivalence threshold when using partial area under the curve (AUC) analyses based on zero to Tmax recommended for highly variable drugs such as epinephrine. Peak plasma epinephrine concentrations for the EpiPen occurred 10 minutes (median Tmax) after dosing, while peak concentrations for the Auvi-Q occurred 20 minutes after dosing. Though bioequivalence may be concluded for Cmax, AUCinf, and AUC0–t, for fast-acting therapeutics used to treat life-threatening conditions, such as epinephrine, additional pharmacokinetic parameters such as AUC zero to Tmax may be important to evaluate when assessing bioequivalence. Keywords: anaphylaxis, therapy, pharmacokinetics, bioavailability, EpiPen, Tmax